Kualitas Situs Web Sebagai Pusat Informasi Pemerintah Dalam Peningkatan Kualitas Pelayanan Publik (Studi pada Situs Web Pemerintah Daerah Kabupaten Tulungagung) - Prihandika Naris Septiawan (Jurnal Administrasi Publik, 2016)
Abstract: Quality Web Site For Information Center of Government Public Service Quality Improvement (Studies in Local Government Website Tulungagung). The local government web sites is the implementation of e-government as a supporter of the performance of community service for 24 hours in order to improve the quality of public services. The results showed that the quality of the website Tulungagung regency administration in terms of eleven parameters are already quite good. Assessment using 11 parameters based on the Local Government website Guidebook Ministry of Communications and inforamsi 2003. Pursuant to 11 the parameters are, the Regional Government website Tulungagung there are still a shortfall in the 5 parameters that context, the size of the quality of interaction, data mobility, public services, hits. Other parameters such as speed, homepage, content, legibility, accuracy and platform has been quite good, but there are some parameters that need to be improved is the content. Found two factors supporting the use of the website as a center of information, namely the factor of leadership and infrastructure. Whereas the inhibiting factor is the factor of human resource constraints and the lack of coordination between agencies so that information is available on the website linked to the existing agencies under the auspices of the Government of Tulungagung still limited. Keywords: Quality Web Site, Information center, www.tulungagung.go.id Tulungagung Abstrak: Kualitas Situs Web Sebagai Pusat Informasi Pemerintah Dalam Peningkatan Kualitas Pelayanan Publik (Studi Pada Situs Web Pemerintah Daerah Kabupaten Tulungagung). Situs web Pemerintah daerah merupakan implementasi e-government sebagai pendukung kinerja pelayanan masyarakat selama 24 jam guna meningkatkan kualitas pelayanan publik. Hasil penelitian menunjukkan bahwa kualitas situs web Pemerintah Daerah Kabupaten Tulungagung ditinjau dari sebelas parameter sudah cukup baik. Penilaian menggunakan 11 parameter situs web Pemerintah Daerah berdasarkan Buku Panduan Kementrian Komunikasi dan Inforamsi tahun 2003. Berdasarkan 11 paramter tersebut, situs web Pemerintah Daerah Kabupaten Tulungagung masih terdapat kekurangan di 5 parameter yaitu konteks, ukuran kualitas interaksi, mobilitas data, layanan publik, hits. Paramater lain seperti kecepatan, hompage, isi, kemudahan dibaca, ketepatan dan platform sudah cukup baik, namun ada beberapa paramater yang perlu ditingkatkan kualitasnya yaitu isi. Ditemukan dua faktor pendukung penggunaan website sebagai pusat informasi yaitu faktor kepemimpinan serta sarana dan prasarana. Sedangkan faktor penghambatnya adalah faktor keterbatasan sumber daya manusia serta kurangnya koordinasi antar instansi sehingga informasi yang tersedia di situs web terkait dengan instansi-instansi yang ada di bawah naungan Pemerintah Kabupaten Tulungagung masih terbatas. Kata kunci: kualitas situs web, pusat informasi, www.tulungagung.go.id Tulungagung